2004
DOI: 10.1073/pnas.0407597101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of dinoflagellate luciferases, enzymes with three catalytic domains in a single polypeptide

Abstract: Enzymes with multiple catalytic sites are rare, and their evolutionary significance remains to be established. This study of luciferases from seven dinoflagellate species examines the previously undescribed evolution of such proteins. All these enzymes have the same unique structure: three homologous domains, each with catalytic activity, preceded by an N-terminal region of unknown function. Both pairwise comparison and phylogenetic inference indicate that the similarity of the corresponding individual domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 36 publications
2
66
0
Order By: Relevance
“…Previous studies revealed that the amount of bias in codon usage varies in the central regions of the domains of the luciferases of the seven photosynthetic dinoflagellates (9,10). The effective numbers of codons is a measure of codon biases (higher value, lower bias).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that the amount of bias in codon usage varies in the central regions of the domains of the luciferases of the seven photosynthetic dinoflagellates (9,10). The effective numbers of codons is a measure of codon biases (higher value, lower bias).…”
Section: Resultsmentioning
confidence: 99%
“…In six other photosynthetic dinoflagellates, the structures of the luciferases were found to be essentially the same as in Lp, and all were found to occur in multiple and tandem copies, albeit with very different intergenic sequences (9,10). In some of these species, a luciferin-binding protein has not yet been found, but in vitro, all react to emit light with the luciferin of Pyrocystis lunula (Pl), which was established to be an open tetrapyrrole (11) and will be called dinoflagellate luciferin.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Dinoflagellates are the only photosynthetic organisms capable of exhibiting bioluminescence (Sweeney 1987), and a number of genera of marine dinoflagellates have been shown to produce light, including Alexandrium Halim. Species within this genus known to be bioluminescent are A. fundyense (Balech) Balech and A. tamarense (Lebour) Balech (Anderson et al 1994), A. affine (Liu et al 2004) and A. catenella (Sullivan and Swift 2003), however, not all clones in a species produce bioluminescence (Anderson et al 1994).…”
Section: Alexandrium Margalefii and Bioluminescencementioning
confidence: 99%
“…So more active sites without more molecules,'' he explains. Postdoctoral fellow Liyun Liu examined luciferases from seven different dinoflagellate species and found them all to be like Gonyaulax: an N-terminal region of unknown function followed by three homologous luciferase domains (23).…”
Section: Three-ring Circusmentioning
confidence: 99%